A Personalized Traditional Chinese Medicine System in the case of Cai's gynecology. (22nd December 2008) - You, Mingyu; Li, Guo-Zheng; Zeng, Xue-Qiang; Ge, Lei; Bi, Lijuan; Huang, Suying; Yang, Mary; Yang, Jack
Diagnostic records of Traditional Chinese Medicine (TCM) practitioners, especially those of masters or veteran practitioners, are precious materials for the TCM researchers and juniors. A novel system (named PTCMS) for preserving the diagnostic processes of veteran practitioners in a personalised way is provided. Based on the summarised TCM specialist's diagnostic template, a custom-built input system embracing the particular expressions of the specialist is set up in the platform. The novel system provides a new way for keeping and researching into the personalised factors in the diagnostic process of TCM masters.